A Novel AP2/ERF Transcription Factor CR1 Regulates the Accumulation of Vindoline and Serpentine in Catharanthus roseus - Liu, Jiaqi; Gao, Fangyuan; Ren, Juansheng; Lu, Xianjun; Ren, Guangjun; Wang, Rui (Frontiers in Plant Science, 2017)
As one type of the most important alkaloids in the world, terpenoid indole alkaloids (TIAs) show a wide range of pharmaceutical activities that are beneficial for clinical treatments. Catharanthus roseus produces approximately 130 identified TIAs and is considered to be a model plant to study TIA biosynthesis. In order to increase the production of high medical value metabolites whose yields are extremely low in C. roseus, genetic engineering combined with transcriptional regulation has been applied in recent years. By using bioinformatics which is based on RNA sequencing (RNA-seq) data from methyl jasmonate (MeJA)-treated C. roseus as well as phylogenetic analysis, the present work aims to screen candidate genes that may be involved in the regulation of TIA biosynthesis, resulting in a novel AP2/ERF transcription factor, CR1 (Catharanthus roseus 1). Subsequently, virus-induced gene silencing (VIGS) of CR1 was carried out to identify the involvement of CR1 in the accumulations of several TIAs and quantitative real-time PCR (qRT-PCR) was then applied to detect the expression levels of 7 genes in the related biosynthetic pathway in silenced plants. The results show that all the 7 genes were upregulated in CR1-silenced plants. Furthermore, metabolite analyses indicate that silencing CR1 could increase the accumulations of vindoline and serpentine in C. roseus. These results suggest a novel negative regulator which may be involved in the TIAs biosynthetic pathway.